PENERAPAN PENDIDIKAN KARAKTER VINSENSIAN (PKV) SEBAGAI MUATAN LOKAL DI SMAK ST. LOUIS 2 SURABAYA - Milawati, Theresia Indri; Widiatna, Alexius Dwi (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2021)
St Louis 2 Catholic High School Surabaya has an unique living because of instilling Vincentian values carried out through Vincentian Character Education. The valeus of St. Vincent A Paulo has been instilling namely humility, simplicity, gentleness, mortification and zeal for souls. This research aimed to explore the efforts to implement Vincentian Character Education as a local content at St Louis 2 Catholic High School Surabaya. The research was conducted using a qualitative approach. Research data collection was carried out using an individual interview tecnique. The research informants were the principal of the school and teachers who are teaching Character Education of Vincentian at St Louis 2 Catholic High School Surabaya. The results of the research show that the implementation of Vincentian Character Education for students at St Louis 2 Catholic High School Surabaya is carried out through an active learning in the classroom as a separated subject of Character Education. The subject has three major points, namely planning, implementation and evaluation.